Komparasi QoS Load Balancing Pada 4 Line Internet dengan Metode PCC, ECMP dan NTH - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Lalu Mutawalli (STMIK Budi Darma, 2022)
The ability to communicate on the internet who do not know the distance and time are the key requirements for improving the work on the internet. To improve performance access to the internet is required solutions as the best of the internet network that can be relied on, so that companies use more than one ISP (Internet Service Provider) to maintain the quality of the internet access with the goal to avoid the interruption of internet access and have backup internet access network if you experience down resulting in disruption of the company's performance in carrying out their duties. One of the contributions of information technology to overcome the merging problems two or more-line internet is a technique of load balancing. This study aims to determine the comparison of QoS load balancing on a 4 line by the method of PCC, ECMP and NTH on real tool MikroTik rb2011UiAS-2HnD. The test method uses speedtest.net from the results it will be seen ping, speed download, speed date, as well as monitoring from the side of the router MikroTik. Stages of research using the method of NDLC (Network Development Life Cycle), namely analysis, design, simulation, prototype, implementation, monitoring and management. With the usefulness of this research is to know the performance resulting from each method of load balancing that is PCC, ECMP and NTH with 4-line internet on MikroTik